2013
DOI: 10.1007/s00418-013-1087-8
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and NUCB2/nesfatin-1 are expressed in the same gastric cell and differentially correlated with body mass index in obese subjects

Abstract: The orexigenic peptide ghrelin and the anorexigenic peptide nesfatin-1 are expressed by the same endocrine cell of the rat stomach, the X/A-like cell. However, data in humans are lacking, especially under conditions of obesity. We collected gastric tissue of obese patients undergoing sleeve gastrectomy and investigated the expression of nesfatin-1 and ghrelin in the gastric oxyntic mucosa by immunofluorescence. Nesfatin-1 immunoreactivity was detected in the human oxyntic mucosa in cells with an endocrine phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 26 publications
1
46
0
2
Order By: Relevance
“…Hence, they can respond to physical stimuli from the lumen, chemical stimuli from the basolateral site, or both and can thus function as endocrine cells delivering ghrelin to peripheral tissues that express GHS-R. Human ghrelin crosses the blood-brain barrier as an intact molecule [3,4]. The ghrelin receptor (GHS-R1a) is conserved across different vertebrate species of mammals, birds and fishes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, they can respond to physical stimuli from the lumen, chemical stimuli from the basolateral site, or both and can thus function as endocrine cells delivering ghrelin to peripheral tissues that express GHS-R. Human ghrelin crosses the blood-brain barrier as an intact molecule [3,4]. The ghrelin receptor (GHS-R1a) is conserved across different vertebrate species of mammals, birds and fishes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed a negative correlation between the cerebrospinal fl uid plasma levels of nesfatin 1 and obesity (16). Increased BMI values indicate reduced orexigenic ghrelin; however, increased anorexigenic nesfatin 1 has been also shown (17). In another study, BMI and weight and nesfatin 1 were reported to be associated with various genetic variations (18).…”
Section: Discussionmentioning
confidence: 96%
“…Recent data provide evidence for a differential regulation of P/D 1 -like cell hormones to counteract further body weight increase. Nesfatin-1 expression increases in obese patients with rising BMI, while acyl ghrelin expression decreases in P/D 1 -like cells [36]. Thus, there are significant findings indicating that P/D 1 -like cells are involved in the regulation of hunger, satiation, and body weight regulation.…”
Section: P/d1-like Cells: Acyl Ghrelin Des-acyl Ghrelin Obestatin mentioning
confidence: 99%